ANALISIS SPIRITUAL ATHEISM DALAM TINJAUAN FILSAFAT JIWA MULLA SADRA - Al Walid, Kholid; Hamdi, Bil (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
This research aims to analyze the perspective of Spiritual Atheism. Philosophically, Spiritual Atheism is grounded in the epistemological framework of empiricism-saintism and the ontological framework of materialism. Its view on spirituality is based on the theory of mind-brain identity and atheistic mystical experiences. The thought framework and arguments of Spiritual Atheism are assessed to contain demarcation problems, contradictions, and limitations of knowledge. Using qualitative methods, literature research, and internal coherence analysis, this study concludes several points. Firstly, the onto-epistemological framework of Spiritual Atheism contains contradictions with its own principles by limiting the entirety of reality and sources of knowledge. Secondly, the theory of mind-brain identity is inadequate because it overlooks the reality of the plurality of consciousness effects that distinguish the soul and body. Lastly, spirituality without God or atheistic mystical experiences in Spiritual Atheism is rejected based on the principle of ittihād al-`āqil wa ma`qūl, which implies the necessity of every soul being connected to God as the efficient cause for all souls in the view of the reality of existence according to Mulla Sadra. Penelitian ini bertujuan untuk melakukan analisis atas pandangan Spiritual Atheism. Secara filosofis, Spiritual Atheism bertumpu pada kerangka epistemologi empirisme-saintisme dan ontologi materialisme. Lalu, pandangannya mengenai spiritualitas bertumpu pada teori identitas pikiran-otak dan pengalaman mistik ateistik. Kerangka pemikiran dan argumentasi Spiritual Atheism dinilai mengandung problem demarkasi, mengandung kontradiksi, dan limitasi pengetahuan. Dengan menggunakan metode kualitatif dan riset pustaka serta analisis koherensi intern, penelitian ini menyimpulkan beberapa poin. Pertama, kerangka onto-epistemologi Spiritual Atheism mengandung kontradiksi dengan prinsipnya sendiri karena melimitasi keseluruhan realitas dan sumber pengetahuan. Kedua, teori identitas pikiran-otak tidak memadai karena mengabaikan kenyataan pluralitas efek kesadaran yang membedakan jiwa dan raga. Terakhir, spiritualitas tanpa Tuhan atau pengalaman mistik ateistik dalam Spiritual Atheism tertolak atas dasar prinsip ittihād al-`āqil wa ma`qūl yang berimplikasi pada keniscayaan setiap jiwa berhubungan dengan Tuhan sebagai kuasa sebab efisien bagi seluruh jiwa dalam pandangan realitas wujud Mulla Sadra.